2014
DOI: 10.4236/ojgas.2014.46039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Venous Ammonia Level, Splenic Longitudinal Diameter, Portal Vein and Splenic Vein Diameters as Non-Invasive Indicators for the Presence of Portosystemic Collaterals in Egyptian Cirrhotic Patients

Abstract: Introduction and Aim of the Work: The identification of cirrhotic patients with esophageal varices or other portosystemic collateral by non-invasive means is appealing in that it could decrease the necessity of endoscopic screening. This study was to evaluate the diagnostic utility of venous ammonia level with other ultrasonographic parameters as non-invasive markers for the presence of portosystemic shunts. Patients and methods: The study included 3 groups of Child Pugh class A and early B patients. Group (A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…SVD of 8.8 mm or more was a good predictor for the presence of OV with 97% sensitivity and 82% specificity. This was matched to findings of Montasser et al [23] who found that splenic vein diameter ≥ 8.9 mm can predict the presence of OV in cirrhotics with 98% sensitivity and 84% specificity.…”
Section: Discussionmentioning
confidence: 55%
“…SVD of 8.8 mm or more was a good predictor for the presence of OV with 97% sensitivity and 82% specificity. This was matched to findings of Montasser et al [23] who found that splenic vein diameter ≥ 8.9 mm can predict the presence of OV in cirrhotics with 98% sensitivity and 84% specificity.…”
Section: Discussionmentioning
confidence: 55%
“…Hypertension of the splenic vein leads to an increased diameter. This causes congestion in the spleen, and consequently, splenomegaly ( Merli et al, 2003 ). Studies have shown that the splenic vein diameter of patients with cirrhosis with HREVs is significantly higher than that of patients with low-risk EVs or healthy controls ( Jamil et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of transition from compensated to decompensated cirrhosis is 5–7% per year ( D'Amico et al, 2006 ). As one of the major complications in patients with cirrhosis, esophageal varices (EVs) occur at a rate of 7–8% per year, which may be higher in patients with decompensated cirrhosis ( Merli et al, 2003 ). Esophageal variceal bleeding (EVB) is a serious and life-threatening complication in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have been performed on this point. El-Hefny et al (23) reported a cutoff value of 77.5 umol/L (108.5 μg/dL) ammonia with 100% sensitivity and 95% specificity for the detection of EV, whereas Tarantino et al 2009 (11) reported a different cutoff value of 42 umol/L (58.8 μg/dL) with a sensitivity 97% and a specificity 43%.…”
Section: Discussionmentioning
confidence: 99%